GAMBARAN PERSEPSI PENGGUNA REKAM MEDIS ELEKTRONIK RAWAT JALAN DI PUSKESMAS - Ahmad Fauzi; Harinto Nur Seha; Nofitriyani Nofitriyani (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
The digitalization of health services is developing very rapidly, marked by the existence of electronic medical records. The implementation of electronic medical records has been required by the government in Minister of Health Regulation number 24 of 2022. Based on the results of a preliminary study at the Berbah Sleman Primary Health Center, there were several obstacles to its implementation, namely related to the internet network and errors in the software which caused the outpatient registration process is stopped. The object of this research is to describe the perceptions of users of outpatient electronic medical records from the perspective of the Technology Acceptance Model (TAM). This type of research is quantitative descriptive by distributing questionnaires to 18 respondents. The results obtained showed that 15 respondents (83%) said it was very good in terms of perceived usefulness, 10 respondents (56%) said it was very easy in terms of perceived ease of use, 18 respondents (100%) said it was very good in terms of perceived behavior intention to use, and as many as 16 respondents (89%) stated that it was very good in terms of actual usage perception. Of the four perceptions which include usefulness, ease of use, behavior intention to use, and actual usage in implementing electronic medical records, users receive it very well.